110k views
1 vote
Please show work!!!!!!!!!

Please show work!!!!!!!!!-example-1
User Dknaus
by
5.1k points

2 Answers

3 votes

Answer:

83 + 12
√(35)

Explanation:

Using the rules of radicals


√(a) ×
√(b)
√(ab)


√(a) ×
√(a) = a

Given

(2
√(5) + 3
√(7)

= (2
√(5) + 3
√(7))(2
√(5) + 3
√(7))

Expand factors using FOIL

= (2
√(5))² + 6
√(35) + 6
√(35) + (3
√(7)

=20 + 12
√(35) + 63

= 83 + 12
√(35)

User Ebensing
by
6.0k points
5 votes

Answer:

83

Explanation:

(2((sqrt)(5))+3((sqrt)(7)))^2

is the same as every individual term inside to the power of 2

(2^2 x (root 5 )^2 + 3^2 x (root 7)^2)

any root squared will become the number inside the root by itself, i.e sqrt of 8^2 will become 8

((4x5) + (9x7))

= 20+63

=83

User Paul Simpson
by
5.4k points